On Subsidising Auto-Commuting - Edward Calthrop (Center for Economic Studies and ifo Institute (CESifo), 2001)
Evidence suggests that a considerable proportion of peak period trips aremade for purposes other than commuting to or from work.given the differentdegrees of Hicksian complementarity with the labour market, optimal taxtheory suggests that, in a second-best world, different trip purposes shouldbe taxed at different rates. This paper explores this issue and argues for auniform congestion toll (independent of trip-purpose) combined with asubsidy to auto-commuters. A numerical model suggests that while, in theabsence of congestion tolls, commuting subsidies are welfare decreasing, anoptimal pricing scheme entails auto-commuters receiving a subsidy of nearly50 percent of the uniform road toll.
Keywords: 330